ANAESTHESIA CHALLENGES DURING MANAGEMENT OF EMERGENCY CESAREAN SECTION IN A POST-PNEUMONECTOMY PRIMIGRAVIDA WITH PLACENTA PREVIA - Chavan, Surekha Sudhir; Raghuvanshi, Amruta Arvind; Gedam, Priyanka H (Bali Journal of Anesthesiology, 2018)
Pulmonary disease is a known risk factor for perioperative respiratory complications. So anesthesiologists are expected to experience these postpneumonectomy patients coming for elective or emergency surgeries. But there is little data to anesthesia management for cesarean delivery of postpneumonectomy parturient. On reviewing the literature, there is only one reported case of the trial of vaginal delivery followed by cesarean section done under epidural anesthesia, a 41 years-old parturient having preoperative respiratory failure and pneumonia in the antenatal period which was managed on continuous positive airway pressure (CPAP) simultaneously. Our case presented a 24 years-old primigravida of 34 weeks gestation with placenta previa and complaints of two days per vaginal bleeding was posted for the emergency cesarean section. She had past history of left lung lobectomy 10 years back, video bronchoscopy 3 years back and history of admission for treatment of an episode of pneumonia at 32 weeks of present gestation. Emergency cesarean section was managed successfully under spinal anesthesia. This case report highlights that spinal anesthesia may remain a good option in anesthesia management for cesarean section in a primigravida with postpneumonectomy.